Analysis of the Effects of Tropical Fruit Extracts on the Physicochemical, Tenderness and Organoleptic Characteristics of Buffalo Meat - Abdurrahman, Faisal; Othman Omar, Othman; Iswadi, Iswadi (Universitas Islam Negeri Ar-Raniry, 2025)
Buffalo meat is an essential protein source in many regions but faces quality challenges, including oxidation, discoloration, and reduced tenderness. This study investigates the impact of soaking buffalo meat in extracts from melinjau, papaya, and pineapple on its physicochemical properties (color, protein, fat content, and tenderness) and organoleptic characteristics (color, aroma, texture, tenderness, and juiciness). Buffalo meat samples were soaked in fruit extracts for varying durations, followed by analysis of color, protein and fat content, tenderness, and sensory qualities. The results showed significant effects of soaking on color, with melinjau and papaya extracts improving lightness and reducing redness. Soaking with papaya and pineapple extracts enhanced tenderness, while melinjau extract increased juiciness. Protein content decreased slightly, but fat content was significantly reduced, particularly with papaya extract. Sensory evaluation revealed that melinjau extract produced the most favorable tenderness and juiciness, while papaya and pineapple extracts also improved tenderness. These findings suggest that tropical fruit extracts can be used to enhance buffalo meat quality by improving tenderness, reducing fat content, and extending shelf life. This natural preservation method offers a potential alternative to synthetic additives, contributing to better sensory properties and higher-quality buffalo meat products.